2020
DOI: 10.38212/2224-6614.3114
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticle-based colorimetric and electrochemical sensors for the detection of illegal food additives

Abstract: Lately, scandals associated with the illegal addition of poisonous chemicals to food for commercial interests have been gradually disclosed to the public. Problems related to food safety do not only harm public health but also affect the stability of economic and social development. Food safety has become a common issue in society, and strengthening the related regulations have become increasingly important. Although conventional techniques are accurate and sensitive in the detection of the vast majority of il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…The unique optical and electrochemical properties of AuNPs [9], as well as their accessibility for various surface functionalizations [10], have been exploited in many applications ranging from diagnostics and cancer therapy [11] to industrial catalysis [12] and water purification [13]. Furthermore, the latest developments in nanotechnology have opened up new opportunities in the food safety industry [14,15] and agronomy [16]. Several studies have shown that biosynthesized AuNPs have larvicidal and nematicidal effects in crop cultivation without adversely affecting their growth and development [17,18], implicating the application of more agro-ecological practices in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The unique optical and electrochemical properties of AuNPs [9], as well as their accessibility for various surface functionalizations [10], have been exploited in many applications ranging from diagnostics and cancer therapy [11] to industrial catalysis [12] and water purification [13]. Furthermore, the latest developments in nanotechnology have opened up new opportunities in the food safety industry [14,15] and agronomy [16]. Several studies have shown that biosynthesized AuNPs have larvicidal and nematicidal effects in crop cultivation without adversely affecting their growth and development [17,18], implicating the application of more agro-ecological practices in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical sensors, with their inherent sensitivity and specificity, are at the forefront of technological advancements designed to safeguard the integrity of the food supply chain, providing consumers and regulatory bodies with the tools necessary to enforce transparency and authenticity in food products. 114 Food fraud detection.-Food fraud, encompassing practices such as adulteration, mislabeling, and substitution, significantly jeopardizes consumer health and erodes trust in the food industry. Electrochemical sensors are powerful tools for addressing these challenges by allowing direct analysis of food composition and the identification of unexpected or unauthorized additives and substances.…”
Section: Applications Of Electrochemical Sensors In Ensuring Food Saf...mentioning
confidence: 99%
“…116 These instances not only underline the prevalence of food fraud but also demonstrate the essential role of advanced detection methods like electrochemical sensors in preventing such deceptive practices and ensuring the authenticity and safety of food products on the market. 114 Geographic origin determination.-Determining the geographic origin of food products is a key aspect of enforcing labeling regulations, protecting regional specialties, and preventing the sale of counterfeit goods. Electrochemical sensors play a critical role in the verification of geographic origin by detecting specific markers or isotopic signatures that are unique to particular regions.…”
Section: Applications Of Electrochemical Sensors In Ensuring Food Saf...mentioning
confidence: 99%
“…Recently, several reviews relating AuNPs-based sensors for food safety 14,27 and disease diagnosis [28][29][30] have been established. However, most of them only focused on colorimetric sensors.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of them only focused on colorimetric sensors. 14,[27][28][29][30] Other types of AuNPs-based optical sensors were mentioned in a few reviews but only as an introduction without full discussion. [28][29][30] This review exhibits a systematic look of AuNPs-based optical sensors for food and health safety monitoring with three kinds of sensors including colorimetric, FRET and SERS sensors.…”
Section: Introductionmentioning
confidence: 99%